2007
DOI: 10.1111/j.1524-4725.2007.33062.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Side effects of Duplex-Guided Sclerotherapy in the Treatment of Great Saphenous Veins with 1% versus 3% Polidocanol Foam: Results of a Randomized Controlled Trial with 1-Year Follow-Up

Abstract: In the treatment of primary incompetent greater saphenous veins, 3% polidocanol foam seems to be more effective than 1% polidocanol foam. The side effects were approximately similar in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 28 publications
6
46
0
7
Order By: Relevance
“…This is somewhat higher than what has been reported in our study. Jia et al [37] showed pain and pigmentations were the two most important complications in foam group which is in accordance with the literature, pain in 4 (16%) patients and pigmentation 5 (20%) patients [51,52].…”
Section: Complicationssupporting
confidence: 82%
See 1 more Smart Citation
“…This is somewhat higher than what has been reported in our study. Jia et al [37] showed pain and pigmentations were the two most important complications in foam group which is in accordance with the literature, pain in 4 (16%) patients and pigmentation 5 (20%) patients [51,52].…”
Section: Complicationssupporting
confidence: 82%
“…The 2% frequency of thromboembolic events in our subjects corresponds to reported thromboembolic event rates between 0.02% and 1.25% [52,53].…”
Section: Complicationssupporting
confidence: 76%
“…Em todos os ensaios a concentração de esclerosante foi de 3%. Um estudo que envolveu um total de 80 doentes e que compara a eficá-cia e efeitos laterais da escleroterapia com espuma a 1 vs. 3% conclui que com uma concentração mais elevada o procedimento parece ser mais eficaz, sendo os efeitos adversos equiparáveis 36 . Portanto, o facto de não ter sido avaliado nenhum ensaio em que fosse utilizado o esclerosante a 1% à partida não altera as conclusões gerais desta revisão.…”
Section: Discussão De Resultadosunclassified
“…For truncal varicosities, a 3% polidocanol foam appears to be more effective than 1% polidocanol foam but may cause more adverse events, such as hyperpigmentation and phlebitis. 16 After injection, patients remain horizontally or in reverse Trendelenburg position to enhance contact for 5 minutes or more. After therapy, cotton wool or foam pads can be applied over the tract of the veins and compression therapy (bandages, antithromboembolism stockings, and/or medical elastic compression stockings class II) are recommended for a period of 1 to 6 weeks.…”
Section: Ultrasound-guided Foam Sclerotherapy (Ugfs) Proceduresmentioning
confidence: 99%